English Courses for Children : Opportunities and Challenges in Educational Entrepreneurship - Ariya Agustin; Muhammad Iqbal (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This study examines the opportunities and challenges in entrepreneurship of English courses for children in Indonesia, focusing on crucial issues such as fierce competition, limited resources, and changes in education policies. The main problem identified is the difficulty of course institutions in attracting parents' attention and retaining qualified teachers. This research aims to provide in-depth insight into market dynamics and strategies that entrepreneurs can apply. The research method used is a demographic study with data collection through questionnaires and semi-structured interviews. The results show that despite the high demand for English language courses, challenges such as competition and resource constraints must be faced with innovation and effective collaboration. The conclusion of this study emphasizes the importance of adaptation and development of appropriate programs to improve the competitiveness of course institutions.